DECONSTRUCTION PERSPECTIVE TOWARDS THE CHARACTERS IN CHRISTINA ROSSETTI’S “GOBLIN MARKET” POEM - M. Bahri Arifin; Singgih Daru Kuncara; Fatimah M. (Fakultas Ilmu Budaya, Universitas Mulawarman, 2019)
Jacques Derrida was the French philosopher and a founding father of deconstruction theory. He challenged the logo-centric Western tradition of the metaphysics of presence. His theory of deconstruction attacked the presuppositions of meaning in a literary works that literary text has conventional or fixed meaning. Deconstruction could bring a new meaning and perspective to Christina Rossetti's poem